Pengaruh Layanan Informasi terhadap Tingkat Kecemasan Mahasiswa Farmasi dalam Mencari Pekerjaan Setelah Lulus - Fitriani, Enny; Asyah, Nur; Fadhillah, Rini; Johannes, Johannes (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
This research was conducted to reduce student anxiety about getting a job after graduating from college through Information Services. This research used an experimental research method. The instrument used in this study was a questionnaire with 40 questions. The population in this study were 56 undergraduate pharmacy students in semesters VI and VIII, while the sample was taken using a total sampling technique, so the sample was 56 students. The data collection used in this study consisted of pretest and post-test data. The hypothesis test uses the two average similarity test (t-test) based on the final data management (post-test) to obtain an average value of 133.71, while the pre-test is 93.96. The results of the t-test hypothesis test show that with a significance level of 5% and 55 degrees of freedom, then 18.2> 1.671, this means that the t-test hypothesis test is that H0 is rejected and H1 is accepted. This study hypothesizes that Information Services positively affect anxiety about getting a job after graduating from college in semesters VI and VIII students of Pharmacy S1.